Kināyah Ayat-ayat Hukum dalam Perspektif Metafora Konseptual - Tantowi, Yusuf Ali; Syihabuddin, Syihabuddin; Sudana, Dadang (Study Program of Arabic Language Teaching, 2025)
This study aims to integrate the analysis of metaphors in the Quran with Conceptual Metaphor Theory (CMT) introduced by Lakoff and Johnson (1980). The primary focus of the research is the analysis of four verses with legal dimensions, recommended by experts in Islamic interpretation and law for their complex metaphorical structure and legal impact. The research uses a descriptive-analytical qualitative approach that emphasizes cognitive linguistics and CMT. Corpus analysis was conducted in two stages: 1) revealing the structure of metaphors based on classical rhetoric, and 2) mapping conceptual metaphors through source and target domains. The main findings indicate that the metaphorical verses in the Quran exhibit a systematic conceptual-cognitive structure. For example, the phrase “aqimu sh-shalah” is interpreted as a metaphor for prayer as a building of faith; the phrase “wa la tas’amu an taktubuhu” represents the documentation of the contract as legally binding; the phrase “libas” is interpreted as a metaphor for the marital relationship, which can be understood across cultures; the phrase “faqtho’u aydiyahuma” represents the elimination of criminal potential. This analysis reveals that kinayah not only serves a rhetorical function but also shapes the conceptual framework of legal understanding. The impact of this research confirms that integrating classical balaghah with CMT can broaden the scope of comprehensive Quranic studies interpretation.